Reformation, resistance, and reason of state (1517-1625) - Mortimer, Sarah (Oxford history political thought, 2021)
This volume charts the development of political thought between 1517-1625. Drawing on a wide range of sources from Europe and beyond, it offers a new reading of early modern political thought, making connections between Christian Europe and the Muslim societies that lay to its south and east.